2010
DOI: 10.1002/chem.200902342
|View full text |Cite
|
Sign up to set email alerts
|

Positionally Isomeric Organic Gelators: Structure–Gelation Study, Racemic versus Enantiomeric Gelators, and Solvation Effects

Abstract: Low molecular weight gelator molecules consisting of aliphatic acid, amino acid (phenylglycine), and omega-aminoaliphatic acid units have been designed. By varying the number of methylene units in the aliphatic and omega-aminoaliphatic acid chains, as defined by descriptors m and n, respectively, a series of positionally isomeric gelators having different positions of the peptidic hydrogen-bonding unit within the gelator molecule has been obtained. The gelation properties of the positional isomers have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…In this regard, solvent polarity, solubility parameters and structural relationships have been investigated. [13][14][15][16][17][18][19][20] These studies highlight the impact that subtle structural modications can have in gelation efficacy. [21][22][23] Despite these efforts and the recent advances in the understanding of kinetic and thermodynamic aspects of the selfassembly process 24,25 it is not yet possible to formulate a model for the design of functional molecular gels.…”
Section: Introductionmentioning
confidence: 96%
“…In this regard, solvent polarity, solubility parameters and structural relationships have been investigated. [13][14][15][16][17][18][19][20] These studies highlight the impact that subtle structural modications can have in gelation efficacy. [21][22][23] Despite these efforts and the recent advances in the understanding of kinetic and thermodynamic aspects of the selfassembly process 24,25 it is not yet possible to formulate a model for the design of functional molecular gels.…”
Section: Introductionmentioning
confidence: 96%
“…In Q. Jin's research, the same gelator molecule can self‐assemble into diverse nanostructures over a wide scale range from nanofibers, nanotwists, to nanotubes and microtubes in different solvents, depending on the solvent polarity and their hydrogen‐bonding nature. Nevertheless, research on solvent‐induced morphology has always focused on common solvents rather than the LCs, which may be due to the lack of knowledge of LCs solvent parameters. Herein, by measuring the solvent polarity of LCs and quantitatively comparing fiber flexibility, we connect solvent polarity with morphology flexibility by a fitting function, which can even be generalized to some common solvents.…”
Section: Introductionmentioning
confidence: 99%
“…The organization in gel assemblies deduced from spectroscopic structural studies are in certain cases closely related to the organizations found in the crystal structures of selected gelators, confirming similar organizations in gel assemblies and in the solid state. Mixing of the constitutionally different bis(amino acid) and bis(amino alcohol)oxalamide gelators resulted, in some cases, in highly improved gelation efficiency denoted as synergic gelation effect (SGE) [11], being also highly dependent on the stereochemistry of the component gelators. Applications of oxalamide units in crystal-and bioengineering may open new perspectives in the utilization of these systems as powerful and versatile organizational and directional element for the future construction of novel abiotic and biotic supramolecular systems.…”
Section: Introductionmentioning
confidence: 99%